Intermediate Structured Finance Modeling: Leveraging Excel, VBA, Access, and Powerpoint - Preinitz, William; Niedermaier, Matthew (Wiley finance series, 2011)
After first outlining the fundamental concepts of asset backed securitisation, this book presents a basic Structured finance model that can be downloaded from the companion website and run in a series of cases.